Seagrass Community in the Coastal Waters of Sapa Village, Tenga District, South Minahasa Regency, North Sulawesi Province - Runturambi, Melinda; Menajang, Febry S. I.; Kondoy, Khristin I.F.; Rembet, Unstain N. W. J.; Manginsela, Fransine B.; Kambey, Alex D. (Sam Ratulangi University, 2023)
Sapa Village, Tenga District, South Minahasa Regency, North Sulawesi Province has a seagrass meadow ecosystem, but there is still a lack of information about the seagrass community in the waters of Sapa Village, which is the reason for researching the presence of seagrass in these waters. With the aim of knowing the types of seagrass, environmental conditions, species density, relative density, domination index, and species diversity index. Based on the results of observations at the location, it showed a temperature of 30OC, salinity of 30‰, pH 8, and sandy substrate and coral rubble. The results of the identification there are 4 types of seagrass namely Thalassia hemprichii, Syringodium isoetifolium, Cymodocea rotundata, and Halodule uninervis. The type with the highest number of individuals vizThalassia hemprichii with a total of 694 individuals, Halodule uninervis 557 individuals, Cymodocea rotundata358 individuals andSyringodium isoetifolium 324 individuals. Density index type (10,80 – 23,13 individuals/m2), relative density (16.76 - 35.90%) dominance index D = 0.32, and diversity H = 1.33. Keywords: seagrass, sapa village, community structure Abstrak Desa Sapa Kecamatan Tenga Kabupaten Minahasa Selatan Provinsi Sulawesi Utara memiliki ekosistem padang lamun namun masih kurangnya informasi mengenai komunitas lamun di perairan Desa Sapa ini menjadi alasan untuk meneliti tentang keberadaan lamun di perairan tersebut. Dengan tujuan untuk mengetahui jenis-jenis lamun, kondisi lingkungan, Kepadatan spesies, Kepadatan Relatif, Indeks Dominasi, dan Indeks Keanekaragaman Spesies. Berdasarkan hasil pengamatan di lokasi menunjukan suhu 30oC, salinitas 30‰, pH 8 dan substrat berpasir serta pecahan karang. Hasil identifikasi terdapat 4 jenis lamun yaitu Thalassia hemprichii, Syringodium isoetifolium, Cymodocea rotundata, dan Halodule uninervis. Jenis dengan jumlah individu terbanyak yaitu Thalassia hemprichii dengan jumlah 694 individu, Halodule uninervis 557 individu, Cymodocea rotundata 358 individu dan Syringodium isoetifolium 324 individu. Indeks kepadatan jenis (10,80 – 23,13 individu/m2), kepadatan relatif (16,76 - 35,90%) indeks dominasi D=0,32 dan keanekaragaman H= 1,33. Kata kunci: lamun, desa sapa, struktur komunitas